Understanding Obstetric Violence as Violence against Mothers through the Lens of Matricentric Feminism - Hill, Nicole (Journal of the Motherhood Initiative for Research and Community Involvement, 2019)
Obstetric violence—that is, the mistreatment or abuse of pregnant, birthing, or postpartum individuals by their maternity care providers, institutions, or systems—is a topic of growing concern around the globe among healthcare organizations, healthcare providers, birthing people, and advocates. As research and advocacy work has begun to denormalize and problematize obstetric violence, it has been framed as a distinct type of institutionalized gendered violence that violates the rights of women. This article approaches the topic of obstetric violence through the lens of matricentric feminism and theorizes how it constitutes not only violence against women (typically) but also violence against mothers. Using examples from my personal experience and recent project, I employ matricentric feminism to emphasize the unique discourses of good and bad motherhood that birthing people engage with and suggest that in the context of obstetric violence, motherhood can be weaponized to perpetuate the invisibility of and silence around this issue. I discuss the implications for an understanding of obstetric violence as violence against mothers, including how these implications may impact efforts to recognize and prevent obstetric violence.